Dietary fiber influence on overall health, with an emphasis on CVD, diabetes, obesity, colon cancer, and inflammation - Alahmari, Layla A. (Frontiers in Nutrition, 2024)
Dietary fiber, found in plant-based foods, plays an essential role in human health. It is divided into two types—soluble and insoluble—both offering significant health benefits. Research has shown that increasing fiber intake can reduce the risk of various chronic diseases, such as cardiovascular diseases (CVD), type II diabetes, obesity, colon cancer, and inflammation. These health conditions are major global challenges, making fiber consumption a key focus for disease prevention. This study reviews a range of clinical trials, cohort studies, and meta-analyses to explore how dietary fiber affects these health risks. By synthesizing data from multiple sources, we found a clear association between higher fiber intake and a lower incidence of these diseases. However, studying the effects of fiber on health presents several challenges. Variations in fiber types and bioavailability make it difficult to generalize results. Additionally, dietary intake is often self-reported, leading to potential inaccuracies in data. Many studies also lack consistency in methodology, and short study durations limit the ability to assess long-term health outcomes. These factors make it harder to draw definitive conclusions about the full range of fiber’s health benefits. Despite these challenges, increasing fiber-rich foods like fruits, vegetables, whole grains, and legumes remains a highly recommended strategy for improving health and reducing the risk of chronic disease.